FACTORS INFLUENCING BUYING INTENTION OF YOUTH TOWARDS THE SUGAR FREE PRODUCTS (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
The paper focus on the causal factors that influence buying intention of sugar free products by youth in India. The study has been conducted in an International University in India among the youth in the age group of 15-40 to elicit the factors that play a positive role in the formation of buying intention of sugar free products. The primary study has been done with the help of a questionnaire after doing a rigorous literature review. The study has considered five influencing factors such as ‘perception, attitude, health reason, healthy lifestyle, and knowledge’ as independent variables and the buying intention as dependent variable. We applied the regression analysis to establish the relationship between influencing factors and the buying intention. Only one independent factor out of five has been found significant in influencing the buying intention of sugar free products. The study has also found that there is no gender difference among the five influencing factors and the buying intention of sugar free products.
Keywords: Sugar free products; Buying intention; Knowledge; Attitude; Perception; Healthy lifestyle